Keberpihakan Hukum Perkawinan di Indonesia Terhadap Hak Perempuan dalam Memilih atau Menolak Perkawinan - Mutrofin, Akmam; Syarifah, Faradhina Millatul Maula (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2024)
Background. ​Indonesian laws and regulations provide protection for women's rights in determining their life partner. However, there are still some parents who still use their ijbar rights to marry off their daughters. Meanwhile, the custom and etiquette of a girl is to obey her parents' orders and she is not allowed to argue in the slightest against her parents' orders, because if a girl refuses, her parents and even the community will label her as a child of disobedience. In fact, after marriage, a woman is no longer the responsibility of the woman's parents, but her husband. However, when a divorce occurs, it is clear that parents will not want to be blamed for the forced marriage they have imposed on their daughter. Aim. This research was conducted with the aim of answering the following questions: (1) Women's Rights in Choosing or Rejecting Marriage, (2) Legal Principles of Partiality KHI Articles 16, 17 and Marriage Law No. 1 of 1974 article 6 Concerning Women's Rights. Method. This research is a type of qualitative research in the form of a research library with a normative approach and library documents as data collection techniques. The data sources were obtained from laws and books and then analyzed using content analysis with an inductive-deductive mindset. Results. The results of this research show that under marriage law in Indonesia a girl has the right to choose her own partner and can also annul a marriage even if her guardian uses his right of consent to marry off an older child. This does not mean eliminating the power of the mujbir guardian because the terms of a marriage still require the presence of a guardian for the bride. This can be shown during the khitbah process, or during the rafa' process in front of the head of the KUA, a bride and groom will need his consent to get married. However, when one of the bride and groom refuses the marriage, the state cannot marry the bride and groom. This is stated in KHI articles 16, 17 and Marriage Law no. 1 of 1974 article 6. The specific principles of marriage (lex specialis) used are the principle of consent, the principle of consent of both parties, the principle of freedom of choice, the principle of eternity in order to achieve a happy marriage.